Who Actually Becomes a Silver Surfer? Prerequisites for Digital Inclusion - Olsson, Tobias; Viscovi, Dino (Javnost-The Public, 2020)
The notion of silver surfers has been recurring in research for two decades. It often refers to elderly skilled and affluent users of digital media. Departing from domestication theory, and drawing on the concept of online repertoires, this article sets out to offer critical insights into what it actually takes, sociologically speaking, to become a silver surfer. The analysis starts from a set of interviews with 19 respondents (66–82 years) covering appropriation and incorporation of digital media and online repertoires. Based on insights from interview data, we turn to a quantitative analysis of a national postal survey (Swedish). In these data (N = 1,264), we first filter out the silver surfers and then perform a logistic regression analysis in order to investigate the factors that promote the status of being a silver surfer. Our analysis shows that only 19% of the sample could be categorised as silver surfers. It further reveals the important influence of factors such as age, income, interest and self-efficacy in particular. Silver surfers are a privileged group. However, contemporary ICT policy tends to assume that they are representative of senior users in general. Thus, there is a significant risk that current policy objectives will be misdirected.